HUBUNGAN ANTARA USIA, MASA KERJA, BEBAN KERJA FISIK, DAN POSTUR KERJA DENGAN KELUHAN MUSKULOSKELETAL PADA PETUGAS PPSU DI KECAMATAN PESANGGRAHAN TAHUN 2023 - Tasbiyatul Husna (2023)
One of the Occupational Diseases (OD) is musculoskeletal complaints, which are health disorders in the muscles, joints, and tendons caused by work activities. PPSU officers in Pesanggrahan District experience musculoskeletal complaints in their lower back and spine. These complaints can decrease productivity at work. The purpose of this study was to analyze the relationship between age, years of service, physical workload, work posture, and smoking habits with musculoskeletal complaints. This study a analytic quantitative with a cross-sectional and chi-square, total sample of 110 workers selected through stratified random sampling. The results of the univariate analysis showed that 96.4% of the PPSU officers had low musculoskeletal complaints. The bivariate analysis indicated no significant relationship between age (p=1.000), length of service (p=0.247), physical workload (p1=0.837; p2=0.549), working posture (p=0,655), and smoking habit (p=0.672) with musculoskeletal complaints. In conclusion, there is no relationship between age, length of service, physical workload, working posture, and smoking habit with musculoskeletal complaints among PPSU officers. However, PPSU officers should be aware of the musculoskeletal complaints they experience and pay attention to maintaining a normal working posture. The sub-district can educate PPSU officers and provide work tools that are in accordance with the worker's body posture.